The candelabra tree (Euphorbia ingens): a source of water for black rhinoceros in Liwonde National Park, Malawi - C.O. Dudley (Koedoe: African Protected Area Conservation and Science, 1997)
The introduction of two rhinoceros into a 15 km2 fenced sanctuary within Liwonde National Park provided an opportunity for close observation of the animals feeding on the toxic succulent Euphorbia ingens. Feeding invariably caused the death of the plant and for plants with basal diameters between 5-17 cm, mortality ranged from 40-90 . During the severe drought of 1994 rhinoceros did not drink from the artificial waterhole from approximately 15 July to at least 23 September. As this waterhole was the only source of free water it is believed that the rhinoceros obtained their water from browsing on E. ingens.